2015
DOI: 10.1080/01496395.2015.1020951
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide and Hexane Extraction of Wax from Apple Peel Pomace: Content, Composition and Thermal Properties

Abstract: Wax of apple peel pomace (WAPP) was obtained from supercritical carbon dioxide (SC-CO 2 ) extraction (SCCE) and hexane extraction (HE), respectively. Characteristics of WAPP, which included extraction yield, chemical composition, thermal properties, and sensory properties, were then analyzed. SCCE and HE reached an extraction yield of 2.081% and 3.975%, respectively. GC/MS results showed that WAPP from SCCE and HE were different in contents and varieties. The differential scanning calorimetry (DSC) thermograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Triterpenic acids are localized mainly in the cuticular waxes protecting the fruit from stress factors [ 7 ]; therefore, the vast majority of them remain in the pomace. Meanwhile, the sterols are present in all cells as a natural constituents of lipid bilayer [ 11 ], thus in the case of cloudy juices only part of them will be found in the pomace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenic acids are localized mainly in the cuticular waxes protecting the fruit from stress factors [ 7 ]; therefore, the vast majority of them remain in the pomace. Meanwhile, the sterols are present in all cells as a natural constituents of lipid bilayer [ 11 ], thus in the case of cloudy juices only part of them will be found in the pomace.…”
Section: Resultsmentioning
confidence: 99%
“…Massias et al [ 10 ] used a mixture of ethanol and CO 2 at 25 MPa and 50 °C for isolation of phenolic compounds. Li et al [ 11 ] compared the isolation of lipids during extraction with hexane and carbon dioxide at 35 MPa and 50 °C; however their work concentrated mainly on the isolation of hydrocarbons. Additionally, two research groups investigated the possibility of using supercritical CO 2 for the removal and analysis of pesticides and fungicides from apple products [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial leftover material in particular, such as peels from juice production, provides raw material for isolating fruit wax compounds. For example, extraction of apple peel pomace using supercritical fluid extraction (SFE) demonstrated the reuse potential of juice industry leftovers as a source for value-added wax (Li et al, 2015). Recently, Tedeschi et al (2018) demonstrated the utilization of fatty acids from tomato pomace waste for production of packaging films.…”
Section: Bioactivity and Commercial Potential Of Waxesmentioning
confidence: 99%
“…The fruit cuticle provides an important physical barrier against pathogens [16] avoiding fungal colonization on sweet oranges [17]. Industrial food wastes such as peels from juice production provide raw material for obtaining wax compounds [18]. The cuticle also provides protection against environmental conditions, where excessive solar radiation produces physiological disorders such as sunscald [19].…”
Section: Introductionmentioning
confidence: 99%